The Communist Party of Yugoslavia during the Autocratic Rule of King Aleksandar Karađorđević - Dušan Bojković (Токови историје, 2015)
This paper presents the results of research made on the stance of the leadership of the Communist Party of Yugoslavia towards the Yugoslav regime during the dictatorship of King Aleksandar Karađorđević, followed by the problem of cooperation between communists and Ustaše and the changes in Party’s territorial organization at the beginning of the 1930s. Both archival and published sources of Party’s central, provincial and regional subdivisions, as well as newspaper articles and relevant literature have been covered in the research.